Liszt Ferenc „Próféta-fantáziá”ja mint orgonamű. Az első kiadás tanulságai - MÉHES, Balázs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Franz Liszt’s Prophet’s Fantasy as an Organ work. Conclusions of the first edition. The piece in the title, dated back in 1850, was a milestone. It is not only the first and most significant organ piece of Liszt, but also one of those pieces which every organist has to deal with sooner or later, and for the interpretation, they have to ask and answer many questions. For this study, the first edition, published in 1852 and available online, provides many references, while the manuscript is difficult to access. It is no coincidence that, at the hundredth anniversary of Bach’s death, Liszt began to write a large-scale organ piece to worship the art of the great composer. It may also be intentional to date the completion of the piece on the Remembrance Day of the Reformation. Both the inevitability of the composition, and the Protestant aspects, and not lastly, the personal commitment of Professor István Dávid to the piece, prompt me to try to find answers to some of the basic questions of this grandiose piece, and publish them – without the need of complete-ness – in the book to be published in honour of him.